Power density vs ionic radii correlations in REBa2Cu3O6+ẟ (RE = La, Nd, Sm, Gd and Y) IT – SOFC potential cathodes - Grassi, Joaquín; Di Benedetto, Natasha; Macías, Mario.A.; Basbus, Juan Felipe; Serquis, Adriana Cristina; Suescun, Leopoldo (Pergamon-Elsevier Science Ltd, 2023)
Fil: Grassi, Joaquín. Universidad de la República; Uruguay